Targeting the nuclear orphan receptor NR4A1: a key target in lung cancer progression and therapeutic resistance - Jin, Minhan; Wang, Yuhui; Song, Mingze; Guo, Wenfei; Li, Shirong; Pu, Zeqing (Frontiers in Oncology, 2025)
As a malignant tumor with high morbidity and mortality, lung cancer is associated with a variety of risk factors, including smoking, exposure to occupational carcinogens, familial inheritance, and chronic lung disease. Lung cancer is often detected late and has a complex pathogenesis, so early diagnosis and intervention of lung cancer are essential. Finding effective targets is important to develop new treatments for lung cancer. As a member of Group 4A of the nuclear receptor subfamily, Nuclear Receptor Subfamily 4 Group A Member 1 (NR4A1) is an immediate early gene that encodes a transcription factor that plays a regulatory role when the cell and tissue microenvironment changes. NR4A1 plays a pro-cancer role in solid tumors including lung cancer, but a tumor suppressor role in hematological malignancies. NR4A1 palys a role through multiple mechanisms in lung cancer, including promoting cell proliferation by forming a complex with p300/specific protein 1 (Sp1) and acting on the survivin and AMP-activated protein kinase (AMPK)/mechanistic Target of Rapamycin Complex 1 (mTORC1) pathways, promoting metastasis and invasion by inducing the occurrence of transforming growth factor-β (TGF-β) dependent epithelial-mesenchymal transition (EMT), promoting vascular remodeling by acting on vascular endothelial growth factor A (VEGF-A), promoting immune escape by acting on programmed cell death-1 (PD-1) dependent T cell exhaustion, promoting cell apoptosis interacted with B-cell lymphoma-2 (Bcl-2) and promoting metabolic reprogramming by increasing fatty acid oxidation. In recent years, several studies on NR4A1-related agonists and inhibitors in lung cancer have been reported. These compounds are expected to become drugs for targeted tumor therapy, but current research is limited to cellular and animal experiments. It still takes time to verify and evaluate clinical applications, other biological effects and potential side effects. This review summarizes the biological role of NR4A1 in lung cancer and describes the molecular mechanisms and signaling pathways regulated by NR4A1. This paper will provide a theoretical basis for the early treatment of lung cancer by using NR4A1-related compounds in the clinic.